2020
DOI: 10.1186/s12917-020-02489-y
|View full text |Cite
|
Sign up to set email alerts
|

A molecular survey and phylogenetic analysis of porcine circovirus type 3 using oral fluid, faeces and serum

Abstract: Background: Porcine circovirus type 3 is the most recently discovered porcine circovirus, and an emerging pathogen. In this study the status of its presence on some Slovenian farms is reported. The effectiveness of the vaccine against porcine circovirus type 2 was assessed against porcine circovirus type 3. Group samples of oral fluid, faeces and individual serum samples were taken from six different pig categories and tested for presence of viral DNA, using both real time and conventional PCR. Positive sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(59 reference statements)
2
4
0
Order By: Relevance
“…Similarly to our results (40%), a Korean study reported a PCV3 prevalence of 44.2% in oral fluid samples [36], and Woźniak et al detected the virus in 37.3% of the oral fluid samples gathered from different Polish herds [40]. On the other hand, Chinese researchers described lower PCV3 prevalence (12.3%) [41], while a study from Slovenia reported a very high detection rate (73%) in this type of sample [39].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly to our results (40%), a Korean study reported a PCV3 prevalence of 44.2% in oral fluid samples [36], and Woźniak et al detected the virus in 37.3% of the oral fluid samples gathered from different Polish herds [40]. On the other hand, Chinese researchers described lower PCV3 prevalence (12.3%) [41], while a study from Slovenia reported a very high detection rate (73%) in this type of sample [39].…”
Section: Discussionsupporting
confidence: 87%
“…Altogether 23% of the serum pools (85/371), 40% of the oral fluid samples (71/176) and 61% of the processing fluid samples (59/97) were positive for PCV3. The detection rates in serum pools are similar to those observed in Poland (25%) [14] and Denmark (30%) but slightly higher than the values reported in Italy (18.18%), Spain (14.89%) [15] or Slovenia (13.1%) [39].…”
Section: Discussionsupporting
confidence: 81%
“…PCV3 was first discovered in 2016 with metagenomic sequencing in domestic swine population in the United States, in cases associated with reproductive failure and PDNS and cardiac and multiorgan inflammation, respectively (Palinski et al, 2017;Phan et al, 2016). Thereafter, PCV3 has been detected, either retrospectively or presently, in Brazil (Tochetto et al, 2018), China (Fan et al, 2017), Italy (Faccini et al, 2017), Poland (Stadejek et al, 2017), South Korea (Kwon et al, 2017), United Kingdom (Collins et al, 2017), Denmark (Franzo, Legnardi, Hjulsager et al, 2018), Japan (Hayashi et al, 2018), Russia (Yuzhakov et al, 2018), Spain (Klaumann et al, 2018), Sweden (Ye et al, 2018), Thailand (Kedkovid, Woonwong, Arunorat, Sirisereewan, Sangpratum, Lumyai et al, 2018), Vietnam (Nguyen et al, 2018), Colombia (Vargas-Bermudez et al, 2019), German (Prinz et al, 2019), Hungary (Deim et al, 2019), Argentina (Serena et al, 2020), India (Bera et al, 2020), Malaysia (Tan et al, 2020), Serbia (Savic et al, 2020), Slovenia (Plut et al, 2020) and Taiwan (Zeng, 2018).…”
Section: Worldwide Detection Of Pcv3mentioning
confidence: 99%
“…Such PCV4 VLPs could enter PK-15 and 3D4/21 cells. Furthermore, PCV4 VLP-specific mouse serum showed limited or no cross-reaction with PCV2 and PCV3, indicating significant potential of PCV4 VLPs in PCV4-specific vaccine development [ 301 ]. An effort to develop soluble chimeric protein consisting of both PCV2d and PCV3 Capsid protein sequences using an E. coli expression system for the purpose of vaccine preparation for PCV2d and PCV3 was also undertaken, but this attempt did not lead to successful solubilization [ 302 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%